2009
DOI: 10.1038/onc.2009.236
|View full text |Cite
|
Sign up to set email alerts
|

NGF inhibits human leukemia proliferation by downregulating cyclin A1 expression through promoting acinus/CtBP2 association

Abstract: Cyclin A1 is essential for leukemia progression, and its expression is tightly regulated by acinus, a nuclear speckle protein. However, the molecular mechanism of how acinus mediates cyclin A1 expression remains elusive. Here we show that transcription corepressor CtBP2 directly binds acinus, which is regulated by NGF, inhibiting its stimulatory effect on cyclin A1 but not cyclin A2 expression in leukemia. NGF, a cognate ligand for the neurotrophic receptor TrkA, promotes the interaction between CtBP2 and acin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…17,[36][37][38] The expression of meiotic genes in nonmeiotic non-germ cell malignancies has been observed with other CTGs, such as SYCP-1 and SPO11, and expression of meiosis-associated genes has been hypothesized to contribute to chromosomal aberrations and therefore support the initiation and further cytogenetic clonal evolution of a malignancy. 39,40 In the case of cyclin-A1 in AML, this mechanism may not apply because, even though expression of cyclin-A1 has been shown to sustain the malignant phenotype, [21][22][23] our recently published data indicated higher cyclin-A1 expression in AML specimens with normal rather than aberrant karyotypes. 20 Furthermore, in case of APL, cyclin-A1 appears to be a target of the RAR-␣ fusion proteins rather than causal for the translocation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,[36][37][38] The expression of meiotic genes in nonmeiotic non-germ cell malignancies has been observed with other CTGs, such as SYCP-1 and SPO11, and expression of meiosis-associated genes has been hypothesized to contribute to chromosomal aberrations and therefore support the initiation and further cytogenetic clonal evolution of a malignancy. 39,40 In the case of cyclin-A1 in AML, this mechanism may not apply because, even though expression of cyclin-A1 has been shown to sustain the malignant phenotype, [21][22][23] our recently published data indicated higher cyclin-A1 expression in AML specimens with normal rather than aberrant karyotypes. 20 Furthermore, in case of APL, cyclin-A1 appears to be a target of the RAR-␣ fusion proteins rather than causal for the translocation.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Cyclin-A1 is aberrantly expressed in AML as well as other malignancies. 16,20 In AML, it can sustain the malignant phenotype through pro-proliferative and antiapoptotic activities, [21][22][23] and overexpression of cyclin-A1 in mice causes dysplastic myelopoiesis with 15% of mice developing transplantable myeloid leukemias. 24 We now show that cyclin-A1 is a testis-leukemia-antigen that harbors a multitude of immunogenic MHC class I epitopes, which can be used to generate T cells from healthy donors that recognize and lyse leukemic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptional control of cyclin A1 has been demonstrated for Sp1 and Sp3, which bind to four GC boxes between nucleotides 2130 and 280 upstream of the transcriptional start site. c-Myc has also been shown to directly transactivate the cyclin A1 promoter and may be involved in the high-level expression of cyclin A1 observed in acute myeloid leukemia (Chan et al, 2009). We now add FoxO3a as a new positive transcriptional regulator of cyclin A1 in ATC.…”
Section: Foxo3a Upregulates Cyclin A1 4259mentioning
confidence: 98%
“…Beside human leukemia, cyclin A1 has been shown to play a role in enhanced cell proliferation in non-small cell lung cancer (Chan et al, 2009;Cho et al, 2006). Because of its selective interaction with CDK and CDC kinases as well as important cell cycle regulators such as E2F1, retinoblastoma (Rb) and the p21 family proteins, screening small compound libraries may identify selective inhibitors of cyclin A1.…”
Section: Foxo3a Upregulates Cyclin A1 4259mentioning
confidence: 99%
“…It has recently been reported that cyclin A1 also contributes to G1-to-S progression of the cell cycle in somatic cells [3], suggesting the functional importance of cyclin A1 in diseases caused by dysfunction of cellular proliferation, such as cancer. Indeed, downregulation of cyclin A1 expression inhibits proliferation of human leukemia cells and induces apoptosis through activation of the DNA-damage response [4,5].…”
Section: Introductionmentioning
confidence: 99%